The Limits of CBR in Software Project Estimation - Delany, Sarah Jane; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 1999)
Software project cost estimation is difficult because of problems of quantifying project size and because of the continual emergence of new technology. This presents as a classic example of a weak theory domain where experience is key and appears well suited to CBR. Indeed there are several reports in the literature on the use of CBR in project cost estimation. Research described to date has focused on applications late in the development life cycle and in a narrow domain. In this paper we describe existing research and explore the use of CBR beyond these limits. We look at the use of CBR for estimation earlier in the life cycle and for use in broader domains where more abstract remindings need to be supported.
Presented at 1998 German Workshop on Case-Based Reasoning
Keywords: Computer Science